Fix Your Membrane Receptor Imaging: Actin Cytoskeleton and CD4 Membrane Organization Disruption by Chemical Fixation - Pereira, Pedro M.; Albrecht, David; Culley, Siân; Jacobs, Caron; Marsh, Mark; Mercer, Jason; Henriques, Ricardo (Frontiers in Immunology, 2019)
Single-molecule localization microscopy (SMLM) techniques allow near molecular scale resolution ( 20nm) as well as precise and robust analysis of protein organization at different scales. SMLM hardware, analytics and probes have been the focus of a variety of studies and are now commonly used in laboratories across the world. Protocol reliability and artefact identification are increasingly seen as important aspects of super-resolution microscopy. The reliability of these approaches thus requires in-depth evaluation so that biological findings are based on solid foundations. Here we explore how different fixation approaches that disrupt or preserve the actin cytoskeleton affect membrane protein organization. Using CD4 as a model, we show that fixation-mediated disruption of the actin cytoskeleton correlates with changes in CD4 membrane organization. We highlight how these artefacts are easy to overlook and how careful sample preparation is essential for extracting meaningful results from super-resolution microscopy.